Educação a distância na sociedade da informação: reflexões acerca dos processos de comunicação, ensino e aprendizagem na sala de aula virtual - Luvizotto, Caroline Kraus [UNESP]; Carniel, Fabiane (My University, 2013)
Information and communication technologies (ICT) pervade the daily lives of people affecting relations and social subsystems. Education is not unrelated to this process and in this scenario the distance education (EaD). Considering as a starting point the information society and its characteristics, the objective of this paper was to analyze the relationship between the new information and communication technologies, teaching and learning in the virtual classroom, seeking to understand what is the design of teaching and learning inherent in the current generation of EaD. Thus, by means of analytical, descriptive and exploratory research, bibliographic and qualitative approach oriented, it was concluded that ICT has a very important role in the context of EaD, allowing the creation of interactive virtual learning environments that enable communication between teachers, tutors and students, making possible the Exchange and sharing of key information on the teaching and learning process.

As tecnologias da informação e comunicação (TIC) permeiam o cotidiano das pessoas afetando as relações e os subsistemas sociais. A educação não está alheia a esse processo e neste cenário destaca-se a Educação a Distância (EaD). Considerando como ponto de partida a sociedade da informação e suas características, o objetivo deste artigo foi analisar a relação entre as novas tecnologias de informação e comunicação, o ensino e a aprendizagem na sala de aula virtual, buscando compreender qual é a concepção de ensino e aprendizagem inerente à atual geração da EaD. Assim, por meio da pesquisa exploratória, descritiva e analítica, de cunho bibliográfico e com abordagem qualitativa, concluiu-se que as TIC têm um papel bastante importante no contexto da EaD, permitindo a criação de ambientes virtuais de aprendizagem interativos, que viabilizam a comunicação entre professores, tutores e alunos, possibilitando a troca e o compartilhamento de informações fundamentais no processo de ensino e aprendizagem.
Distance education in the information society: reflections on the processes of communication, learning and teaching in the virtual classroom
Keywords: Distance education; The information society; Information and communication Technologies; Teaching and learning process; Virtual classroom; Educação a Distancia; Sociedade da informação; Tecnologias de Informação e Comunicação; Processo ensino-apendizagem; Sala de aula virtual